The effect of moderate hypothermia on the electrographic seizure burden in neonatal hypoxic ischaemic encephalopathy. (7th June 2011) - Lowe, E; Mathieson, S; Stevenson, N; Murray, D; Rennie, J; Boylan, G
Abstract : Background: Moderate therapeutic hypothermia improves outcome in babies with hypoxic ischaemic encephalopathy by reducing neuronal damage during the reperfusion stage at which time seizures often commence. Some evidence suggests seizures may cause additional damage beyond the original insult via excitotoxic effects. We used continuous electroencephalography (EEG) to compare the seizure burden in a group of hypothermic (HT) babies against a normothermic (NT) group to examine the effects of cooling on seizure burden. Methods: Continuous video-EEG was started as soon after birth as possible and recorded for a minimum of 20 h. Two experienced encephalographers marked the beginning and end of each seizure and the number of seconds of seizure/hour was calculated. Results: A total of 31 babies with seizures were recorded, 15 NT and 16 HT. Recordings were started earlier and recorded for longer in the HT group, Despite this increased facility to record seizures, the seizure burden was significantly lower in the HT group than the NT group who had shorter seizures for less time. The median seizure burden during the entire EEG period in the HT group was 60 (39–224) min compared to 203 (141–206) min in the NT group. Conclusion: There is a reduced seizure burden in babies with HIE who are cooled. The beneficial effects of therapeutic hypothermia may in part be mediated via a reduction in the excitotoxic effects of seizures.